Review paperSuicidal ideation and behaviour in dermatological patients - Korabel, Hanna; Dudek, Dominika; Jaworek, Andrzej; Wojas-Pelc, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
Dermatological disorders are a less common direct cause of patients’ death than internal organ diseases. Nevertheless, some patients with skin disorders commit suicide successfully. Psychodermatology is a new part of medicine, which combines dermatology, psychology and psychiatry. The incidence of psychiatric disorders among dermatological patients is estimated at 30 to 60%. Because dermatology is a very specific branch of knowledge, it is necessary to know the suicidal part of dermatological diseases. Psychodermatology is the branch of medicine that describes the interaction between dermatology and psychiatry. Skin lesions are visible and they may influence the patient’s psyche. Psychological factors are important in the pathology of several dermatoses. The article presents a review of the literature concerning the suicidal ideation and behaviour among dermatological patients.